Effects of chemical absorption on mass transfer from single carbon dioxide bubbles in aqueous sodium hydroxide solution in a vertical pipe. (14th December 2021) - Sa'adiyah, Devy Setiorini; Matsuo, Yuki; Schlüter, Michael; Kurimoto, Ryo; Hayashi, Kosuke; Tomiyama, Akio
Highlights: Mass transfer from single CO2 bubbles in NaOH solutions is measured. Experimental condition covers various bubble shapes. Effects of chemical absorption on mass transfer are discussed. Empirical correlation of the enhancement factor is proposed. Abstract: Mass transfer rates kL of single carbon-dioxide bubbles with chemical absorption in a vertical pipe were investigated using aqueous sodium hydroxide solutions. The pH of the solution was varied from 12 to 13.15. The pipe diameter D was 12.5 mm. The bubble diameter d was varied for 0.4 < d/D < 1.4 to cover various bubble shapes. The enhancement factor, E, which is the ratio of kL with and without chemical absorption, was almost unity for pH < 12.25. Then E increased with increasing pH and d for pH > 12.25. Its magnitude was, however, lower than the estimation by the two-film theory. An E correlation was developed. Good estimation of the Sherwood number for bubbles with chemical absorption was obtained by combining the E correlation and the Sherwood number correlations for bubbles without chemical absorption. Applicability of the correlations to bubbles in a larger pipe diameter was also examined.